The Influence of Religiosity on Well-Being and Acceptance in Parents of Children with Autism Spectrum Disorder - White, Stacy E. (Journal of religion, disability & health, 2009)
This study was designed to investigate religiosity, parental well-being, stressors in raising a child with autism, and acceptance of the disorder. Previous research states that religiosity can buffer the effects of stressors on well-being (Friedrich et al., 1988), and provide support and peace of mind (Tarakeshwar and Pargament, 2001). Parents of children with autism (n = 177) participated by completing an Internet-based questionnaire. Results revealed correlations between most of the variables, and the association between stress and well-being was stronger for parents with lower religiosity. Implications for parents and religious organizations and directions for future research are discussed.